Cellular stress due to impairment of collagen prolyl hydroxylation complex is rescued by the chaperone 4-phenylbutyrate - Roberta Besio; Nadia Garibaldi; Laura Leoni; Lina Cipolla; Simone Sabbioneda; Marco Biggiogera; Monica Mottes; Mona Aglan; Ghada A. Otaify; Samia A. Temtamy; Antonio Rossi; Antonella Forlino (The Company of Biologists, 2019)
Osteogenesis imperfecta (OI) types VII, VIII and IX, caused by recessive mutations in cartilage-associated protein (CRTAP), prolyl-3-hydroxylase 1 (P3H1) and cyclophilin B (PPIB), respectively, are characterized by the synthesis of overmodified collagen. The genes encode for the components of the endoplasmic reticulum (ER) complex responsible for the 3-hydroxylation of specific proline residues in type I collagen. Our study dissects the effects of mutations in the proteins of the complex on cellular homeostasis, using primary fibroblasts from seven recessive OI patients. In all cell lines, the intracellular retention of overmodified type I collagen molecules causes ER enlargement associated with the presence of protein aggregates, activation of the PERK branch of the unfolded protein response and apoptotic death. The administration of 4-phenylbutyrate (4-PBA) alleviates cellular stress by restoring ER cisternae size, and normalizing the phosphorylated PERK (p-PERK):PERK ratio and the expression of apoptotic marker. The drug also has a stimulatory effect on autophagy. We proved that the rescue of cellular homeostasis following 4-PBA treatment is associated with its chaperone activity, since it increases protein secretion, restoring ER proteostasis and reducing PERK activation and cell survival also in the presence of pharmacological inhibition of autophagy. Our results provide a novel insight into the mechanism of 4-PBA action and demonstrate that intracellular stress in recessive OI can be alleviated by 4-PBA therapy, similarly to what we recently reported for dominant OI, thus allowing a common target for OI forms characterized by overmodified collagen. This article has an associated First Person interview with the first author of the paper.